Imagining Chinese Medicine - Lo, Vivienne; Barrett, Penelope (Sir Henry Wellcome Asian Series, 2018)
A remarkable journey through Chinese medical illustrations from the earliest illustrated manuscripts to advertising and comic books. Senior and emerging scholars from Asia, Europe and the Americas rethink the history of medicine, its epistemologies and materialities, challenging Eurocentric narratives. Readership: All interested in Chinese medicine and the history of illustration, the transmission of Chinese medical knowledge and ideas along the Silk Roads and maritime routes.